181k views
4 votes
Solve the initial value problem

y′′+4y′+40y=0

y(0)= 3
y′(0)=5.

1 Answer

6 votes

Answer:

The solution is
y(t) = 3e^(-2 t)cos(6 t) + (11)/(6) e^(-2 t)sin(6 t)

Explanation:

First we will write the characteristic equation, which is


x^(2) + 4x + 40 = 0

This is a quadratic equation

For the general form of quadratic equation,
ax^(2) +bx + c = 0,
x is given by the general formula,


x = \frac{-b+\sqrt{b^(2) - 4ac } }{2a} or
x = \frac{-b-\sqrt{b^(2) - 4ac } }{2a}

Hence, for
x^(2) + 4x + 40 = 0


a = 1, b = 4, and
c = 40

Hence, the formula becomes


x = \frac{-4+\sqrt{(4)^(2) - 4(1)(40) } }{2(1)} or
x = \frac{-4-\sqrt{(4)^(2) - 4(1)(40) } }{2(1)}


x = (-4+√(16 - 160) )/(2) or
x = (-4-√(16 - 160) )/(2)


x = (-4+√(-144) )/(2) or
x = (-4-√(-144) )/(2)


x = (-4+ 12i )/(2) or
x = (-4- 12i )/(2)


x = -2 + 6i or
x = -2 - 6i

Hence,
x = -2 ±
6i

That is,
x_(1) = -2 + 6i or
x_(2) = -2 - 6i

These are the roots of the equation.

For the general solution,

Since the roots of the equation are complex,

If the roots of a characteristic equation are in the form
(\alpha ±
\beta i), then the general solution is given by


y(t) = C_(1)e^(\alpha t)cos(\beta t) + C_(2)e^(\alpha t)sin(\beta t)

Hence, the general solution for the differential equation becomes


y(t) = C_(1)e^(-2 t)cos(6 t) + C_(2)e^(-2 t)sin(6 t)

Then


y'(t) = -2C_(1)e^(-2t) cos(6t) - 6C_(1)e^(-2t) sin(6t) -2C_(2)e^(-2t)sin(6t) + 6C_(2)e^(-2t) cos(6t)

Now, from the question,

y(0)= 3

y′(0)=5.

That is,


3 = y(0) = C_(1)e^(-2(0))cos(\beta (0)) + C_(2)e^(-2(0))sin(\beta (0))


3 = C_(1)e^(0)cos(0) + C_(2)e^(0)sin(0)


3 = C_(1)


C_(1) = 3

[NOTE:
e^(0) = 1 and
cos(0) = 1 and
sin(0) = 0 ]

Also,


5 = y'(0) = -2C_(1)e^(-2(0)) cos(6(0)) - 6C_(1)e^(-2(0)) sin(6(0)) -2C_(2)e^(-2(0))sin(6(0)) + 6C_(2)e^(-2(0)) cos(6(0))


5 = -2C_(1) + 6C_(2)

Now, we can find
C_(2) by putting the value of
C_(1) = 3 into the equation


5 = -2C_(1) + 6C_(2)


5 = -2(3) + 6C_(2)


5 = -6 + 6C_(2)\\11 = 6C_(2)\\C_(2) = (11)/(6)


C_(1) = 3 and
C_(2) = (11)/(6)

Then the solution becomes


y(t) = 3e^(-2 t)cos(6 t) + (11)/(6) e^(-2 t)sin(6 t)

User Loushou
by
6.0k points